The effect of medical malpractice liability on rate of referrals received by specialist physicians. Issue 4 (26th March 2013) - Xu, Xiao; Spurr, Stephen J.; Nan, Bin; Fendrick, A. Mark
Abstract Using nationally representative data from the United States, this paper analyzed the effect of a state's medical malpractice environment on referral visits received by specialist physicians. The analytic sample included 12, 839 ambulatory visits to specialist care doctors in office-based settings in the United States during 2003–2007. Whether the patient was referred for the visit was examined for its association with the state's malpractice environment, assessed by the frequency and severity of paid medical malpractice claims, medical malpractice insurance premiums and an indicator for whether the state had a cap on non-economic damages. After accounting for potential confounders such as economic or professional incentives within practices, the analysis showed that statutory caps on non-economic damages of 250, 000 were significantly associated with lower likelihood of a specialist receiving referrals, suggesting a potential impact of a state's medical malpractice environment on physicians' referral behavior.